Pacific Alliance: Bringing Back Open Regionalism to Latin America - Gonzalez-Perez, Maria Alejandra; Gutiérrez-Viana, Santiago; Rodríguez-Rios, Juan David; Gutiérrez-Gómez, Laura (México y la Cuenca del Pacífico, 2015)
This paper seeks to answer why the Pacific Alliance (PA) has emerged as the latest integration initiative in the already wide spectrum of multilateral groups in Latin America. It does so by evaluating the political and economic considerations that motivated the pa’s formation, aiming to present informed arguments within the framework of trade and political developments in the region. This paper is based on both secondary and primary data (interviews), and it is divided into four parts plus conclusions. The paper starts by presenting a general characterization of the Alliance; afterwards, presents a historic and comparative overview of the integration processes in the region; assesses the current level of integration between the pa members; and, finally, offers insights into future developments in the following areas: transnational production chains, access to foreign markets and extra-regional (economic and political) outreach. The results of this study show how the public and private sector’s experience in international trade and international business has motivated the members of the Pacific Alliance to join forces to consolidate a platform for economic integration allowing them to increase market access, foster economic growth, and improve human development indicators in the region. From the political point of view, the paper concludes that the pa emerged as a liberal counterpart to the left-leaning integration initiatives that had been prevalent in the region during the preceding decade. La Alianza del Pacífico: el regreso del regionalismo abierto a América Latina. En el presente artículo se busca responder por qué la Alianza del Pacífico (AP) ha surgido como la más reciente iniciativa dentro del ya amplio espectro de agrupaciones multilaterales en América Latina. Para ello, en el documento se evalúan las consideraciones políticas y económicas que motivaron la formación de la ap, presentando argumentos informados en el marco de los desarrollos comerciales y políticos en la región. Este documento se basa en fuentes tanto primarias (entrevistas) como secundarias y se divide en cuatro secciones, más conclusiones. En primer lugar se presenta una caracterización general de la Alianza del Pacífico; en seguida se presenta un resumen histórico y comparativo de la ap con otras iniciativas regionales de integración; se evalúa el grado de integración que se ha alcanzado hasta el momento entre los países miembros Mayo-agosto de 2015. Análisis 23 Pacific Alliance: Bringing Back Open Regionalism to Latin America de la ap, y finalmente se ofrecen perspectivas sobre los futuros desarrollos en las siguientes áreas: cadenas transnacionales de valor, acceso a mercados extranjeros y diversificación de las relaciones económicas y políticas de sus miembros. Los resultados de este estudio sugieren que la experiencia de los sectores público y privado en materia de comercio intrarregional motivó a los países de la Alianza a aunar esfuerzos para consolidar una plataforma de integración económica que les permitiese potenciar el acceso a mercados, fortalecer el crecimiento económico y mejorar los indicadores de desarrollo humano en la región. Desde el punto de vista político, el documento concluye que la ap surgió como una alternativa liberal frente a las iniciativas de integración de corte izquierdista que fueron prevalentes en la década precedente.